Radical cystectomy in eldery - Bančević, Vladimir; Aleksić, Predrag; Milović, Novak; Spasić, Aleksandar; Kovaćević, Božidar; Toševski, Perica; Čampara, Zoran; Milošević, Radovan; Cerović, Snežana (Vojnosanitetski pregled, 2015)
Background/Aim. Radical cystectomy is the method of choice for the treatment of muscle invasive bladder cancer. This major surgery is associated with many complications, especially in older patients. The aim of this study was to analyze preoperative comorbidity, and intraoperative and postoperative complicatons in patients older than 75 years. Methods. This clinical, retrospective study included 46 patients over 75 years, who underwent radical cystectomy. Indications for surgery, and complications during and after the surgery were followed up. Results. Preoperatively, anemia caused by hematuria was registered in 76% of the patients. In 52% of the patients urine derivation was performed by ileal conduit, in 35% by ureterocutaneostomy and in 13% orthotopic ileal neobladder was created. The average duration of surgery was 190 (120–300) min. A total of 76% of the patients were treated by blood supstitution intraoperatively, average 630 (310–1230) mL. Concerning pathological stage of transitional cell carcinoma of urinary bladder, 26% of the patients had T2, 4% T3a, 52% T3b, and 14% T4a stage. In one case, planocellular carcinoma was diagnosed by patohistological examination, and in 2 cases prostate carcinoma was incidentally found. The average duration of hospitalization was 16 (8–35) days. Conclusion. The main reason for cystectomy in patients over 70 and 80 years was gross hematuria caused by bladder cancer, with consecutive anemia which could not be solved using endoscopic treatment or blood supstitution. As expected, a prolonged stay in hospital after cystectomy, and a higher rate of complications were recorded in this population.
Keywords: urinary bladder neoplasms; cytectomy; aged; hematuria; comorbidity; postoperative complications